Structural Model of Antecedents and Consequences of Inpatient Satisfaction at dr. M. Haulussy Ambon Regional Hospital - Luhulima, Vinsa Delia; Zacharias, Tehubijuluw; Selanno , Hendry (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the structural model of antecedents and consequences of inpatient satisfaction at RSUD dr. M. Haulussy Ambon. The research approach used is quantitative, associative with cross-section data collection, and ex post facto methods. The population used in this study were all non-BPJS inpatients at RSUD dr. M. Haulussy Ambon during June-August 2024. The sample determination was purposive as many as 100 non-BPJS inpatients at RSUD dr. M. Haulussy Ambon. Data were analyzed using path analysis.The results of the study indicate that (1) the patient satisfaction variable empirically becomes an intervening variable that is able to mediate service quality, hospital image and price perception towards the trust and loyalty of inpatients; (2) patient satisfaction variables do not only act as independent or dependent variables but are able to act as variables that are able to mediate the involvement of antecedent variables to consequence variables; (3) service quality, hospital image and price perception are antecedent variables to patient satisfaction: (4) inpatient trust and loyalty are consequence variables of patient satisfaction.